2001
DOI: 10.1002/bdm.369
|View full text |Cite
|
Sign up to set email alerts
|

Averaging probability judgments: Monte Carlo analyses of asymptotic diagnostic value

Abstract: Wallsten et al. (1997) developed a general framework for assessing the quality of aggregated probability judgments. Within this framework they presented a theorem regarding the effects of pooling multiple probability judgments regarding unique binary events. The theorem states that under reasonable conditions, and assuming conditional pairwise independence of the judgments, the average probability estimate is asymptotically perfectly diagnostic of the true event state as the number of estimates pooled goes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…Moreover, although a person's ability to choose the higher expected value gamble was diminished with small samples, our analysis showed that small samples are not ruinous to choosing the higher expected value gamble. Johnson, Budescu, and Wallsten (2001) reported an analogous result when aggregating probability judgments to form a new probability judgment: judges can be quite accurate when averaging very few judgments. Before we describe testable implications of the amplification effect, let us briefly turn to how the difference between options relates to difficulty of choice and to choice strategies.…”
Section: The Amplification Effect: How Substantial and How Costly Is It?mentioning
confidence: 81%
“…Moreover, although a person's ability to choose the higher expected value gamble was diminished with small samples, our analysis showed that small samples are not ruinous to choosing the higher expected value gamble. Johnson, Budescu, and Wallsten (2001) reported an analogous result when aggregating probability judgments to form a new probability judgment: judges can be quite accurate when averaging very few judgments. Before we describe testable implications of the amplification effect, let us briefly turn to how the difference between options relates to difficulty of choice and to choice strategies.…”
Section: The Amplification Effect: How Substantial and How Costly Is It?mentioning
confidence: 81%
“…As we have demonstrated, awareness of one's vulnerability to bias is an important antecedent of openness to advice that in turn affects decision quality. Research maintains that integrating advice from external sources improves decision making (Larrick and Soll 2006, Johnson et al 2001, Budescu and Rantilla 2000, Yaniv 2004; see Bonaccio and Dalal 2006 for a review). People high in bias blind spot, for example, may be particularly likely to ignore the advice of peers or experts when engaging in financial or medical decision making and require alternative forms of guidance to improve the quality of their decisions.…”
Section: Consequences and Implications Of The Bias Blind Spotmentioning
confidence: 99%
“…A general conclusion from this work is that some form of averaging describes very well the observed behavior in most cases (e.g., Clemen, 1989;Fischer & Harvey, 1999;Wallsten, Budescu, & Tsao, 1997). The accuracy of the average opinion increases monotonically as a function of the number of advisors, but at a diminishing rate that depends on the inter-judge correlation (e.g., Ariely et al, 2000;Clemen & Winkler, 1985;Hogarth, 1978;Johnson, Budescu, & Wallsten, 2001;Wallsten & Diederich, 2001). Although under certain circumstances, averaging is also normatively optimal, people fail to appreciate the benefits of this simple aggregation rule (Larrick & Soll, 2006).…”
Section: Accuracy Of and Confidence In Aggregationmentioning
confidence: 99%